PENGARUH PENGGUNAAN STRATEGI SELF-MANAGEMENT DALAM KONSELING KELOMPOK TERHADAP KECEMASAN BELAJAR SISWA KELAS VIII SMP JALAN JAWA - Hermanto, Rendy Jauhari (HELPER, 2017)
Abstract The research method which is used is post experimental with one group pre test post test design. The research sample is 20 students class VIII SMP JALAN JAWA Surabaya which is taken by purposive sampling technique. Data collection technique uses measuring scale which had been done validity test and realiability test alpha cronbach. Validity test of measuring scale study anxiety is between 0,531-0,945, while reliability test alpha cronbach is 0,682. Pretest data and posttest are analyzed by using SPSS for windows version 22 by technique T test statistic parametric after had been done normality assumption test and homogeneities variant. Based on the analysis result, can be concluded that “there is positive influence significantly of using strategy self-management in group counseling to study anxiety of students class VIII SMP JALAN JAWA Surabaya”. Keyword: Self Management, Group Counseling, Anxiety